ARE RESIDENTS IN URBAN AREAS OF NIGERIA EXPOSED TO HEALTH-IMPACTING LEVELS OF NOISE POLLUTION? - Anejionu, Obinna C.D.; Ebinne, Elijah S.; Nwosu, Kelechi I.; Anejinou, Miriam G. U.; Ndukwu, Raphael I. (UI Scholars Hub, 2022)
Across the world urban dwellers are facing increasing risks of exposure to noise pollution. The World Health Organization (WHO) described noise pollution as an underestimated threat that can cause various health problems to humans and wildlife. In Nigeria, urban areas are experiencing increasing levels of noise pollution. In this study, a combination of low-cost noise sensors and GIS modelling were used to conduct a preliminary investigation of the spatiotemporal patterns of noise pollution in a prominent urban area in Nigeria. This was to ascertain whether residents are exposed to dangerous noise levels that could affect their health as well as to demonstrate the potentials of deploying network of sensors for real-time monitoring of noise pollution in urban areas of developing countries. We observed noise levels at 5 seconds intervals, over a period of 24 hours, at different strategic locations (e.g. Achara Layout, Abakpa, and Independence Layout) across the city. Using GIS analytics techniques, data obtained from field were used to produce noise maps of the city. We found that night-time noise levels ranged between 32 and 35dBA, which are below recommended limits by the Nigerian government and WHO. Daytime noise levels ranged between 44 and 66dBA, slightly exceeding recommended limits. This contradicts general perceptions that noise levels in the city are dangerously high. This study has given the first insight into the spatiotemporal patterns of noise levels across Enugu Metropolis. It is the first time a spatiotemporal study of noise pollution was conducted in the city, revealing noise footprints of various parts of the city.